Tribological properties of nanometer Al2O3 and nanometer ZnO as additives in lithium-based grease. Issue 6 (13th August 2018) - He, Qiang; Wang, Zhigang; Li, Anling; Guo, Yachen; Liu, Songfeng
Abstract : Purpose: Nanoparticles as the grease additives play an important role in anti-wear and friction-reducing property during the mechanical operation. To improve the lubrication action of grease, the tribological behavior of lithium-based greases with single (nanometer Al2 O3 or nanometer ZnO) and composite additives (Al2 O3 –ZnO nanoparticles) were investigated in this paper. Design/methodology/approach: The morphology and microstructure of nanoparticles were characterized by means of transmission electron microscope and X-ray diffraction. Tribological properties of different nanoparticles as additives in lithium-based greases were evaluated using a universal friction and wear testing machine. In addition, the friction coefficient (COF) and wear scar diameter were analyzed. The surface morphology and element overlay of the worn steel surface were analyzed by scanning electron microscopy (SEM) and energy dispersive spectrometer (EDS), respectively. Findings: The results show that the greases with nanometer Al2 O3 or nanometer ZnO and the composite nanoparticles additives both exhibit lower COFs and wear scar diameters than those of base grease. And the grease with Al2 O3 –ZnO composite nanoparticles possesses much lower COF and shows much better wear resistance than greases with single additives. When the additives contents are 0.4 Wt.% Al2 O3 and 0.6 Wt.% ZnO, the composite nanoparticles-based grease exhibits the lowest mean COF (0.04) and wear scar diameter (0.65 mm), which is about 160% and 28% lower than those of base grease, respectively. Originality/value: The main innovative thought of this work lies in dealing with the grease using single or composite nanoparticles. And through a serial contrast experiments, the anti-wear and friction-reducing property with different nanoparticles additives in lithium grease are evaluated.